Bioactive compounds in cheeses: biosynthesis, biological activity, and contribution of lactic acid bacteria - López-Mendoza, Joel; Adriano-Anaya, Lourdes; Gálvez-López, Didiana; Vázquez-Ovando, Alfredo (Agronomía Mesoamericana, 2023)
Introduction. Since 1990, there has been an increase in the rate of diseases associated with unhealthy diets and sedentary lifestyles, whose care is a challenge for health systems. This has aroused interest in functional foods, i.e., those that in addition to providing macro and micronutrients, provide substances that have a physiological effect on the body, which translates into improving the health of those who ingest them. Generically, these compounds are known as bioactives. Objective. To review the main bioactive substances reported in cheeses, as well as the role of microorganisms in their production and the biosynthetic routes of the main compounds. Development. Milk and its derivatives are food products consumed around the world and show a constant increase in their production and consumption. This market trend is due to its flavor and nutritional value. One of the most demanded dairy products in the world are cheeses. They are a source of substances such as peptides, fatty acids, vitamins, bacteriocins, organic acids, gamma aminobutyric acid, etc. all with important biological activity. Conclusion. The presence, quantity, and availability of the bioactive compounds present in the cheeses differ, as a result of the type of milk used for its elaboration, the type of microorganism used, either as starter or secondary culture, as well as the technological process employed.